Stolen words - Florence, Melanie (Second Story Press, 2017)
"This picture book explores the intergenerational impact of Canada's residential school system that separated Indigenous children from their families. The story recognizes the pain of those whose culture and language were taken from them, how that pain is passed down and shared through generations, and how healing can also be shared. Stolen Words captures the beautiful, healing relationship between a little girl and her grandfather. When she asks him how to say something in his language - Cree - her grandpa admits that his words were stolen from him when he was a boy. The little girl then sets out to help her grandfather regain his language."--Publisher's description.